Investigating the sources of poverty in the informal settlements using Greenwell Matongo as a laboratory test ground. - Ogbokor, Cyril A.; Ngeendepi, Elson J. (Bethany Books, 2011)
Poverty is undoubtedly one of the main challenges facing mankind. In this study Questionnaires were designed and used to collate relevant data and subsequently analyzed. The findings of the study indicate that most informal settlement breeds poverty and the following factors were implicated as accounting for the high degree of poverty in the informal settlements: Unemployment, low literacy rate, the absence of basic infrastructures, including low income levels. The study recommends various interventionist policies that could be used to address and possibly ameliorate the magnitude of poverty currently eating deep into the Namibian society. The paper concluded by encouraging other social researchers to carry out more studies regarding the issue of poverty in Namibia.
Keywords: Poverty - Namibia; Informal settlements - Namibia; Greenwell Matongo neighbourhood, Katutura, Namibia